Composition and structure of bismuth doped dysprosium manganite - Mataev, M.M.; Saksena, S.M.; Patrin, G.S.; Tursinova, Zh.I.; Kezdikbayeva, A.T. (Ye.A.Buketov Karaganda State University Publ., 2018)
In the present work, the multiferroic material Bi0.8Dy0.2MnO3 was synthesized by the Pechini method for its further study. As starting materials, bismuth oxide, manganese oxide, dysprosium oxide, nitric acid and urea were used.It is shown that when nitric acid and urea are used as a precipitant, single-phase powders can be obtained. The powder was sintered at various temperatures of 600 ºC, 800 ºC, 900 ºC, respectively, in order to evaluate their optimum sintering temperature based on X-ray profiles. The incorporation of Bi3+ ions into the perovskite crystal structure was verified by means of X-ray, SEM methods. The XRD revealed that the obtained nanocrystalline Bi0.8Dy0.2MnO3 was cubic crystal structure of space group: Fm-3m(225) and lattice parameters were: 5.4763 Å, 5.4763 Å, 5.4763 Å, 90.000, 90.000, 90.000. The density of manganite was determined by the pycnometric method in accordance with State Standard 2211–65. Toluene served as an indifferent fluid. Satisfactory consistency of X-ray and pycnometric densities of manganite confirms the correctness of the results. The results of the electron microscope show that the atomic fractions of the elements practically coincide, which corresponds to the formula of manganite-BDMO.
Висмутпен легирленген диспрозий манганитінің құрамы жəне құрылысы
Состав и структура легированного висмутом манганита диспрозия
Keywords: manganite of bismuth; doping; Pechini method; multiferroic; electron microscope; nanocrystal; cubic; liquid-phase process